Cognitive Levels of Questions By Indonesian Teachers of English - Fani Febriyana; Ignatius Harjanto (Yayasan Visi Intan Permata, 2023)
According to the 2013 English curriculum (K-13), teachers were required to create English test items covering higher-order thinking skills (HOTS). By answering HOTS questions, students are expected to understand information deeper rather than only focusing on recalling facts. This case study aimed to find the cognitive levels of questions used in teacher-made English final tests in a private senior high school in Sampit, Central Kalimantan, Indonesia. Using the revised Bloom's taxonomy, this qualitative study investigated the written documents of teacher-made English final tests for grades X and XI in the academic years 2018-2019 for social and science programs. The findings showed that the cognitive levels of questions in the final test were dominated by the lower order of thinking skills (LOTS), with understanding as the highest level, followed by remembering and applying. The researchers identified potential sources of preference for LOTS questions. The paper concludes with research recommendations and a professional development program for English teachers.